Psychosocial support during displacement due to a natural disaster: relationships with distress in a lower-middle income country. Issue 6 (26th February 2019) - Zahlawi, Tatiana; Roome, Amanda B; Chan, Chim W; Campbell, Jacqueline J; Tosiro, Bev; Malanga, Max; Tagaro, Markleen; Obed, Jimmy; Iaruel, Jerry; Taleo, George; Tarivonda, Len; Olszowy, Kathryn M; et al.
Abstract: Background: Past studies show relationships between disaster-related displacement and adverse psychosocial health outcomes. The development of psychosocial interventions following displacement is thus increasingly prioritized. However, data from low- and middle-income countries (LMICs) are lacking. In October 2017, the population of Ambae Island in Vanuatu, a lower-middle income country, was temporarily displaced due to volcanic activity. We analyzed distress among adults displaced due to the event and differences based on the psychosocial support they received. Methods: Data on experiences during displacement, distress and psychosocial support were collected from 443 adults 2–3 wk after repatriation to Ambae Island. Four support categories were identified: Healthcare professional, Traditional/community, Not available and Not wanted. We analyzed differences in distress by sex and group using one-way ANOVA and generalized linear models. Results: Mean distress scores were higher among women (1.90, SD=0.97) than men (1.64, SD=0.98) (p<0.004). In multivariate models, psychosocial support group was associated with distress among women (p=0.033), with higher scores among women who reported no available support compared with every other group. Both healthcare professional and traditional support networks were widely used. Conclusions: Women might be particularly vulnerable to distress during disaster-related displacement in LMICs, and those who report a lack of support might be at greater risk. Both healthcare professional and traditional networks provide important sources of support that are widely used and might help to ameliorate symptoms.